Construction supply chain management: a scoping review - Krainer, Jefferson Augusto; Krainer, Christiane Wagner Mainardes; Vidolin, Ana Celia; Hasse, Frank Kiyoshi; Romanel, Fabiano Barreto; Romano, Cezar Augusto (Ambiente Construído, 2021)
Studies related to construction supply chain management (CSCM) emerged in the mid-1990s to address the structural, economic and organizational nature typical of the construction industry. Previous researches sought to review the literature on CSCM, however, they usually focused on specific and well-defined issues. This article aimed to map the current areas and subareas of the CSCM. Adopting a bibliometric approach and following the PRISMA-ScR recommendations, a scoping review was carried out. With the help of the CiteSpace© tool, the information was viewed as a co-citation network, providing a panoramic view of how the main publications are distributed and networked, forming research areas and subareas. The key documents and the main authors were identified; the current situation and the emerging points of interest in the CSCM field were also revealed. This article establishes a knowledge base for future research, which can help scholars and managers to identify authors, documents and journals to be considered when dealing with certain topics of the CSCM.